2010
DOI: 10.1177/147323001003800630
|View full text |Cite
|
Sign up to set email alerts
|

An Interesting Entity Mimicking Malignancy: Laryngeal Candidiasis

Abstract: Primary candidiasis in the laryngeal mucosa is rare but has many predisposing factors, in particular immune insufficiency and long-term antibiotic use. This study involved a reassessment of 530 laryngeal biopsy specimens originally examined between 2004 and 2009, from which 11 cases of hyperplastic laryngeal candidiasis were identified according to their clinical and histopathological features. Among possible predisposing factors, immune insufficiency was identified in three patients, there was long-term antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…In the present study, the male/female ratio in the group with candida leukoplakia was 26 to 10, and the number of males was higher. This result was similar to those of other studies performed in the same georaphy 6,10 ; however, in other countries, different results were obtained. 8,9 Although there is no definite explanation of gender-related difference, it is thought that the difference may have stemmed from the fact that patients living in different regions might have different sociodemographic characteristics and lifestyles.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the present study, the male/female ratio in the group with candida leukoplakia was 26 to 10, and the number of males was higher. This result was similar to those of other studies performed in the same georaphy 6,10 ; however, in other countries, different results were obtained. 8,9 Although there is no definite explanation of gender-related difference, it is thought that the difference may have stemmed from the fact that patients living in different regions might have different sociodemographic characteristics and lifestyles.…”
Section: Discussionsupporting
confidence: 91%
“…Of the 36 patients in the Candida group, 26 (72.2%) were male, and 10 (27.8%) were female. In case series in the literature, while Pabuççuoglu et al 6 and Saraydaroglu et al 10 reported that vocal fold laryngeal candidiasis was more common among males, Sulica 8 and Wong et al 9 reported that it was more common among females. In the present study, the male/female ratio in the group with candida leukoplakia was 26 to 10, and the number of males was higher.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, given the patient’s recent diagnosis of oropharyngeal carcinoma, there was also a definite need to consider tumour recurrence despite initial biopsy showing granulation tissues with no neoplasia. There have been prior case reports of laryngeal candidiasis mimicking possible malignancy [19], [20], [21].…”
Section: Discussionmentioning
confidence: 99%
“…Histologically, some cases of CHC may mimic squamous cell carcinoma (Saraydaroglu et al, 2010 ; and, in particular, verrucous carcinoma. Some authors suggest that those cases that exhibit pronounced epithelial hyperplasia and/or verrucous carcinoma-like features should be extensively searched for hyphae or yeasts (Pabuççuoglu et al, 2002 ) in order to avoid the misdiagnosis of dysplasia or malignancy.…”
Section: Histopathological Characteristicsmentioning
confidence: 99%